Analysis of Challenges and Opportunities for Improving the Health System in Afghanistan: Innovative Approaches and Sustainable Solutions - YAR, Fayaz Gul Mazloum (PT Batara Swastika Harati, 2024)
This research explores the challenges and opportunities for improving the health system in Afghanistan. The healthcare system is critical to any country's social and economic development. Equitable and comprehensive access to health and medical services is vital for public health and plays a crucial role in improving quality of life, reducing poverty, and enhancing workforce productivity. Afghanistan, a country that has experienced decades of war, political instability, and economic crises, faces significant challenges in healthcare. The main objective is to identify the important issues within the healthcare system and propose sustainable solutions to enhance the quality of health services. Using a mixed-method approach (qualitative and quantitative), data were collected through semi-structured interviews with experts and a review of credible scientific sources. The findings indicate that a lack of healthcare infrastructure, a shortage of specialized human resources, and management issues are among the primary challenges facing Afghanistan's healthcare system. Additionally, opportunities such as international support and utilizing modern technologies in healthcare have been identified. The study concludes that investment in infrastructure, human resource training, and strengthening international collaborations is essential to improve the healthcare situation in Afghanistan.